Teaching Oral and Powerpoint Skills for the Surgical Morbidity and Mortality (M&M) Conference Presentation - Irena Gribovskaja-Rupp; Philip Redlich; Robert Treat; Travis Webb; Rebecca Anderson (Association of American Medical Colleges, 2013)
Abstract This resource teaches first- and second-year surgical residents how to develop an oral PowerPoint presentation in the style of a surgical morbidity and mortality conference. The resource consists of multiple steps, starting with an individual presentation session. In addition, the program emphasizes critical evaluation of self- and peer presenters in a group setting of up to 16 learners. Learners also receive constructive criticism from faculty in a nonthreatening classroom environment that enhances group dynamics and promotes teamwork. Constructive, professionally phrased feedback is emphasized and practiced by the group participants. This resource has been used for over 5 years at our institution. Residents have rated this resource as 4.1-4.8 on a 5-point scale over many sessions. Overall, this resource was designed to improve the oral presentation skills of junior residents in order to prepare them for morbidity and mortality and departmental conferences. Because of this resource, our residents have developed an awareness of their presentation style and improved multiple aspects of it, specifically reducing the amount of distracting language and mannerisms and improving the effectiveness of their presentations. They have learned to be appropriately self-critical and to provide professionally worded oral and written feedback to their peers in a group setting.